ANALISIS VALIDITAS RELIABILITAS TINGKAT KESUKARAN DAYA PEMBEDA SOAL ASESMEN SUMATIF BAHASA JAWA SEKOLAH DASAR (SD) DI KABUPATEN KENDAL - Trimo (Widya Aksara : Jurnal Agama Hindu, 2025)
The aim of the research is to evaluate the quality of the summative assessment questions for the Javanese Language subject at the elementary school level in Kendal Regency in the academic year 2023/2024. The focus of the research is to analyze the validity, reliability, difficulty level, and the discriminating power of the questions. The method of the study belongs to quantitative with a descriptive approach. Data were obtained from question documents and student answer sheets, which were then analyzed using item analysis techniques. The results of the study show that the questions have high validity with the majority of the items meeting the established criteria. The reliability of the questions is also in a good category indicating consistency to measure students' abilities. Most of the questions have a moderate difficulty level which makes them suitable for learning evaluation. Additionally, the discriminating power of the questions is fairly good with the ability to differentiate between high-ability and low-ability students Based on the research findings, it can be concluded that the Javanese Language Summative Assessment questions in Kendal Regency have met good quality standards. However, some items still need to be revised to improve their effectiveness. This study recommends that question designers should pay more attention to aspects of validity, reliability, difficulty level as well as discriminating power to prepare evaluation questions in the future.